DIVERSITY OF IPOMOEA IN GETAP, CAKRANEGARA, MATARAM CITY - Siratul Aini; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
Lombok is one of the islands in the Lesser Sunda Islands, home to a rich biodiversity, including plants. This research is necessary to determine the diversity of Ipomoea plants in Getap. Research shows that two Ipomoea species are present in Getap: Ipomoea batatas and I. aquatica.